Heritage Productions (African Knowledges and the History Publication since the 1970s)
Talk about African heritage and film-making, as well as the educational potentials of film.
Keywords: Interviews; Cultural Heritage; African Cultural Heritage; Film Production; Black People; Race Identity; Black People in Film